Identification of a DYRK1A Inhibitor that Induces Degradation of the Target Kinase using Co-chaperone CDC37 fused with Luciferase nanoKAZ - Sonamoto, Rie (Sci Rep, 2015)
The protein kinase family includes attractive targets for drug development. Methods for screening of kinase inhibitors remain largely limited to in vitro catalytic assays. It has been shown that ATP-competitive inhibitors antagonize interaction between the target kinase and kinase-specific co-chaperone CDC37 in living cells. Here we show a cell-based method to screen kinase inhibitors using fusion protein of CDC37 with a mutated catalytic 19-kDa component of Oplophorus luciferase, nanoKAZ (CDC37-nanoKAZ). A dual-specificity kinase DYRK1A, an importance of which has been highlighted in Alzheimer’s disease, was targeted in this study. We established 293T cells stably expressing CDC37-nanoKAZ, and analyzed interaction between CDC37-nanoKAZ and DYRK1A. We revealed that DYRK1A interacted with CDC37-nanoKAZ. Importantly, point mutations that affect autophosphorylation strengthened the interaction, thus improving signal/noise ratio of the interaction relative to non-specific binding of CDC37-nanoKAZ. This high signal/noise ratio enabled screening of chemical library that resulted in identification of a potent inhibitor of DYRK1A, named CaNDY. CaNDY induced selective degradation of DYRK1A, and inhibited catalytic activity of recombinant DYRK1A with IC(50) value of 7.9 nM by competing with ATP. This method based on a mutant target kinase and a bioluminescence-eliciting co-chaperone CDC37 could be applicable to evaluation and development of inhibitors targeting other kinases.